Selenium nanoparticles induce coumarin metabolism and essential oil production in Trachyspermum ammi under future climate CO2 conditions - Aloufi, Fahed A (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.